Konstruksi dan Identifikasi Properti Psikometris Instrumen Pengukuran Kebahagiaan Berbasis Pendekatan Indigenous Psychology: Studi Multitrait‐Multimethod - Wahyu Jati Anggoro; Wahyu Widhiarso (Jurnal Psikologi, 2010)
The aim of this study was to develop a scale of happiness based on indigenous psychology approach and identify it’s psychometric properties. The research was divided into three step of scenario: 1. happiness construct exploration based on indigenous psychology approach; 2. Develop the construct into a scale of happiness (Likert model); and 3. Identify it’s psychometric properties (reliability and validity). The psychometric properties analyses consist of internal consistency reliability (alpha‐Cronbach) and construct validity (convergent‐discriminant). Multitrait‐multimethod matrix was used on the analysis in order to identify the convergent‐discriminant validity (including three comparative scales: Self‐Esteem Scale Rosenberg, Self‐Esteem Inventory Coopersmith, and PGC Morale Scale). The exploration result shows a unique indicators of happiness in the East native culture (N=604). The psychometric properties analysis show the alpha reliability α=0.895 and the validity was psychometrically accepted (N=111). The conclusion of this study: happiness is a unique construct that consist of strong contextual aspects and the measurement of a native happiness should used a scale of happiness that based on indigenous psychology approach. Further result will be discussed.